Tin-assisted heteroepitaxial PLD-growth of κ-Ga2O3 thin films with high crystalline quality - M. Kneiß; A. Hassa; D. Splith; C. Sturm; H. von Wenckstern; T. Schultz; N. Koch; M. Lorenz; M. Grundmann (APL Materials, 2019)
High-quality Ga2O3 thin films in the orthorhombic κ-phase are grown by pulsed-laser deposition using a tin containing target on c-sapphire, MgO(111), SrTiO3(111), and yttria-stabilized ZrO2(111) substrates. The structural quality of the layers is studied based on the growth parameters employing X-ray diffraction 2θ-ω scans, rocking curves, ϕ scans, and reciprocal space maps. Our layers exhibit superior crystalline properties in comparison to thin films deposited in the monoclinic β-phase at nominally identical growth parameters. Furthermore, the surface morphology is significantly improved and the root-mean-squared roughness of the layers was as low as ≈0.5 nm, on par with homoepitaxial β-Ga2O3 thin films in the literature. The orthorhombic structure of the thin films was evidenced, and the epitaxial relationships were determined for each kind of the substrate. A tin-enriched surface layer on our thin films measured by depth-resolved photoelectron spectroscopy suggests surfactant-mediated epitaxy as a possible growth mechanism. Thin films in the κ-phase are a promising alternative for β-Ga2O3 layers in electronic and optoelectronic device applications.